Drivers of Green Consumerism: The Role of Eco Branding and Beliefs in the Nepalese Urban Market - Manandhar, Alisha; Bhandari, Badri Prasad (Journal of Kapan Multiple Campus, 2025)
This study focuses on how green marketing affects consumers' purchasing behaviour in Nepal. The study provides the theoretical understanding of consumer purchasing decisions for green products in Kathmandu Metropolitan City by examining five major elements: Environmental beliefs, Eco labeling, Eco branding, Green products, and Green packaging, which were conducted through an extensive review of various literature. A descriptive study was done in order to obtain the results. The data were quantitative in nature, and it was collected using convenience sampling. Responses that met the validity criteria for the study were 390, of which 415 questionnaires were distributed. The survey was done using an online questionnaire, using Google Forms, and the data were processed and analyzed using Microsoft Excel and SPSS software. The study’s findings indicate that green marketing positively and significantly influences customer purchasing decisions, with eco branding having the most effect. However, green products do not significantly affect consumers’ decisions to purchase eco-friendly items. According to the survey, consumers’ purchasing decisions are significantly influenced by green marketing.